2002
DOI: 10.1197/aemj.9.2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Depressive and Alcoholic Symptoms and Aggressive Behavior in Adult Male Emergency Department Patients

Abstract: Abstract. Objective: To determine the extent to which depressive and alcoholic symptoms are related to aggressiveness in male emergency department (ED) patients. Methods: A cross-sectional survey design was conducted in a Midwest urban ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Two questions were used to assess parent alcohol use: ‘How often do you drink alcohol?’ with answers ranging from never to nearly every day and ‘How often in the last month have you had five or more drinks on one occasion?’ which defines binge drinking. Parents were asked to respond to one statement addressing anger/frustration: ‘I feel frustrated or angry’ with response categories of never, sometimes, always (Bacaner et al . 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Two questions were used to assess parent alcohol use: ‘How often do you drink alcohol?’ with answers ranging from never to nearly every day and ‘How often in the last month have you had five or more drinks on one occasion?’ which defines binge drinking. Parents were asked to respond to one statement addressing anger/frustration: ‘I feel frustrated or angry’ with response categories of never, sometimes, always (Bacaner et al . 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Across multiple samples of men, the variables identified as potential predictors of IPV perpetration have been found to be quite broad, and have included: being young; being married to or living with a partner, or both; reporting a high number of sexual partners; having fathered 3 or more children; adhering to traditional gender norms and belief in male dominance; having antisocial personality characteristics; being an ethnic/racial minority; having a drinking or drug use problem, or both; having combat-related posttraumatic stress disorder; and experiencing current depression. [8][9][10][11][12][13][14][15][16][17] Some investigators suggested that many predictor variables (e.g., age, ethnicity/race) could be indicators for other more-primary variables such as socioeconomic status. 17 And there was contradictory evidence about some variables, such as race/ethnicity; for example, the 1992 National Crime Victimization Survey found no statistically significant differences in IPV victimization rates across ethnic groups.…”
Section: Introductionmentioning
confidence: 99%